2010
DOI: 10.1021/np1005746
|View full text |Cite
|
Sign up to set email alerts
|

Daphnane- and Tigliane-Type Diterpenoid Esters and Orthoesters from Pimelea elongata

Abstract: Investigation of Pimelea elongata ("Lakebed Pimelea") afforded 18 tigliane- and daphnane-type diterpenes (1-18). Eight of these were new compounds: four (1-3, 5) tigliane esters and four (7, 8, 10, 11) daphnane orthoesters. The 10 known compounds were 12-O-decanoylphorbol-13-acetate (4), P. simplex subtoxin B (6), wikstroelide E (9), pimelotides A and B (12, 13), gnidiglaucin (14), simplexin (15), huratoxin (16), kirkinine D (17), and 12-β-acetoxyhuratoxin (18). The structures and relative configurations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 34 publications
1
36
0
2
Order By: Relevance
“…The NOESY correlations of H-7/H-8, H-7/H-20b, H-8/H-11, and H-8/H-14 indicated that H-7, H-8, H-11, H-14 and H-20b were assigned in β -orientations. A literature survey revealed that when the absolute configuration of C-9′ was R , correspondingly, 10′-CH 3 was in the α -orientation of the molecule, the chemical shift of C-10′ would appear around δ C 19.0 [ 12 , 13 ]; if the C-9′ was S configuration, the C-10′ would shift downfield to δ C 12.3 [ 4 , 5 , 13 ]. The chemical shift of C-10′ δ C 19.1 in 1 suggested the R configuration of C-9′ in 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The NOESY correlations of H-7/H-8, H-7/H-20b, H-8/H-11, and H-8/H-14 indicated that H-7, H-8, H-11, H-14 and H-20b were assigned in β -orientations. A literature survey revealed that when the absolute configuration of C-9′ was R , correspondingly, 10′-CH 3 was in the α -orientation of the molecule, the chemical shift of C-10′ would appear around δ C 19.0 [ 12 , 13 ]; if the C-9′ was S configuration, the C-10′ would shift downfield to δ C 12.3 [ 4 , 5 , 13 ]. The chemical shift of C-10′ δ C 19.1 in 1 suggested the R configuration of C-9′ in 1 .…”
Section: Resultsmentioning
confidence: 99%
“…As confirmed from the molecular formula, the 1 H and 13 C NMR revealed that the aliphatic chain of compounds 4 and 5 contained two more and four more methylene groups than mellerin B respectively. By detailed MS and NMR data analysis, compound 4 was identified as simplexin, a known compound previously isolated from the genus Pimelea (Thymelaeaceae) including P.simplex and P. elongata and other plant species (Asada et al, 2011;Hayes et al, 2010). Compound 5 was identified as montanin, from its MS and NMR data analysis and also in comparison with data from literature.…”
Section: Characterisation Of Compounds From the Stem Bark Extractmentioning
confidence: 90%
“…Hirseins A and B have shown inhibition of melanogenesis in B16 murine melanoma cells [22]. Glabrescin( 12 ) and Montanin ( 26 ) have been obtained from Neoboutoniaglabrescens [23]. Kirkinine D ( 25 ) and synaptolepisfactor K 7 ( 28 ) have been isolated from the S.kirkii [24].…”
Section: Species Of Daphnane-type Diterpenoids and Their Bioactivementioning
confidence: 99%